Relationship between the use of antibiotics and anti-pain in breast cancer patients (ca mammae) - Mohamad Rizky; Lidya Angelina Rotua; Windiyani Nur'amanah Suharmin; Ratni Kaino; Defita Zubaidi (Institute of Computer Science (IOCS), 2023)
The most common cancer detected in women is breast cancer. After lung cancer, it is the most frequent reason for cancer-related mortality. This is because patients who have advanced breast cancer seek medical attention. The lack of understanding about breast cancer and how to do breast self-examination (BSE) for early identification of breast cancer among the general population contributed to the delay in treatment. This research aimed to ascertain how patients with Camamae used antib iotics and painkillers in connection to one another. This kind of research is retrospective, descriptive, and utilizes secondary data. Patients diagnosed with breast cancer between January 2019 and December 2023 were selected from medical records at the Regional General Hospital dr. Hasri Ainun Habibie as a research subject. The results obtained from medical records show that the relationship between painkillers and antibiotics is very important where giving painkillers to breast cancer patients is to improve the patient's quality of life, especially for patients who have experienced arrest or removal of breast tissue while giving antibiotics is to prevent exposure to bacteria when it will be carried out profit and after done.